Verdant edges: mapping vegetation health temporal changes in Bulakan’s emerging coastal aerotropolis - Rayco, Gilbert Matthew; Santos, Selena Balbino; Villa Juan, Jose Dan (Jurnal Pembangunan dan Alam Lestari, 2026)
The development of the New Manila International Airport (NMIA) in the Municipality of Bulakan, Bulacan, has generated complex socio-environmental challenges, including livelihood displacement, intensifying pollution, and rapid population growth. As a large-scale coastal infrastructure project, NMIA exerts considerable pressure on existing ecosystems, particularly on the integrity and health of surrounding vegetation. In response, this study evaluates the implications of NMIA development on vegetation dynamics using a Normalized Difference Vegetation Index (NDVI) temporal analysis at a regional scale. Multi-temporal satellite imagery was analyzed to capture changes in vegetation greenness across three critical phases: pre-construction, initial development, and the current stage of expansion. To provide a more comprehensive spatial understanding, landscape metrics were integrated with Geographic Information System (GIS)-based techniques to assess patterns of fragmentation, patch distribution, and ecological connectivity. The findings reveal pronounced fragmentation within the inner core zone, where vegetation patches have become increasingly degraded and spatially simplified. In the intermediate zone, patch structures exhibit a gradual reduction and transition, indicating ongoing ecological stress. Conversely, the outer gradient demonstrates a more coalesced landscape pattern, characterized by relatively lower levels of fragmentation and higher continuity of vegetative cover. These results suggest that NMIA construction has significantly altered vegetation structure, particularly in areas closest to development activities, thereby reducing ecological resilience in the coastal environment. Given these impacts, the study underscores the importance of adopting a region-wide, vegetation-sensitive landscape planning approach. Such an approach is essential to balance infrastructure development with ecological sustainability and to support the long-term viability of Bulakan’s emerging coastal aerotropolis